Prevalence and characterisation of antimicrobial resistant Enterobacteriaceae in fresh vegetables from farm to retail in the Gauteng Province of South Africa - Korsten, Lise (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2022